2012
DOI: 10.2174/1876142911204010050
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Hypoglycemic Effects of Five Commonly Used Herbal Food Supplements

Abstract: Hyperglycemia is a pathological condition associated with prediabetes and diabetes. The incidence of prediabetes and diabetes is increasing and imposes great burden on healthcare worldwide. Patients with prediabetes and diabetes have significantly increased risk for cardiovascular diseases and other complications. Currently, management of hyperglycemia includes pharmacological interventions, physical exercise, and change of life style and diet. Food supplements have increasingly become attractive alternatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…This agrees with the results of previous studies that have shown that other food-based antioxidants can improve glycemic control in healthy subjects as in those with T2DM [13,14,16,18]. Research suggests that antioxidants may reduce blood glucose levels by affecting carbohydrate digestion in the small intestine due to inhibition of α-glucosidase in gut mucosa [19,23] or inhibition of -amylase, a key enzyme for breaking down starch [23].…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with the results of previous studies that have shown that other food-based antioxidants can improve glycemic control in healthy subjects as in those with T2DM [13,14,16,18]. Research suggests that antioxidants may reduce blood glucose levels by affecting carbohydrate digestion in the small intestine due to inhibition of α-glucosidase in gut mucosa [19,23] or inhibition of -amylase, a key enzyme for breaking down starch [23].…”
Section: Discussionsupporting
confidence: 91%
“…Many medicinal plants are known to have an effect on glucose metabolism [27]. In this study, methanolic leaf extract C. volkensii did not cause either hypoglycemia or hyperglycemia.…”
Section: Steroids -mentioning
confidence: 44%
“…Patients with prediabetes and diabetes have significantly increased risk for cardiovascular diseases and other complications. Currently, management of hyperglycemia includes pharmacological interventions, physical exercise, and change of lifestyle and diet (Deng, 2012). The use of orthodox drugs in the management of diabetes mellitus has not improved the situation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the existing drugs for the treatment of diabetes mellitus do not satisfy our need completely, the search for new drugs continues. Food stuffs and supplements have increasingly become attractive alternatives to prevent or treat hyperglycemia, especially in subjects with mild hyperglycemia (Bhutkar, Bhise, 2011;Deng, 2012). Therefore, there has been increasing demand for the use of plant products and food stuffs with antidiabetic activity due to low cost, easy availability and lesser side effects.…”
Section: Introductionmentioning
confidence: 99%